Evaluating Bengkulu culture’s role in mathematics learning outside classrooms for understanding measurement - Yumiati, Yumiati; Rodríguez-Nieto, Camilo Andrés; Bonyah, Ebenezer; Sudirman, Sudirman; Haji, Saleh (Institute of Advanced Engineering and Science, 2024)
Connecting measurement concepts from informal to formal situations was challenging for students, specifically in understanding length and area measurements in elementary school. The use of cultural context in mathematics learning have been identified as a potential solution to address these challenges, although further exploration was required. Therefore, this study aimed to investigate the impact of mathematics learning designs outside classroom that integrate the culture of Bengkulu, Indonesia. A quasi-experimental design was used with a total of 83 fifth-grade students from two medium- and high-level elementary schools. The assessment instrument comprised six test questions and an observation sheet to record students’ activities. The results showed that students in high-level schools understood teacher instructions and worksheets more quickly, providing additional time for measuring practice. Conversely, students at medium-level schools tended to wait for instructions. The inferential analysis showed that integrating mathematics learning designs outside classroom in Bengkulu cultural context did not significantly increase the understanding of area and length measurements for students in medium-level schools but positively impacted those in high-level schools. Therefore, this method had the potential to improve understanding of other mathematical concepts, specifically when effectively implemented in schools with higher levels of understanding.